The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0034-72802012000100005
|View full text |Cite
|
Sign up to set email alerts
|

Condições visuais autorrelatadas e quedas em idosos institucionalizados

Abstract: Objetivo: Avaliar as condições visuais autorrelatadas por idosos institucionalizados e sua relação com acidentes por quedas. Métodos: Estudo prospectivo em que foram entrevistados 59 idosos residentes em instituições de longa permanência para idosos, em Goiânia, GO, entre 2005 e 2007. Foram realizados dois inquéritos com intervalo de dois anos para realização das avaliações propostas. As condições visuais no primeiro inquérito e o relato de quedas no seguimento foram autorrelatadas. Os idosos foram classificad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
0
7
1
11
Order By: Relevance
“…Literature also describes a high frequency of auditory and visual deficit among the elderly 11,12 , a fact that while not quantified in the present study, was observed, though not described. Reports of embarrassment at initiating and maintaining conversations and avoiding leaving home were constant, which can lead to social isolation, loss of occupational roles, mobility limitations, fragility and dependence.…”
Section: Discussioncontrasting
confidence: 46%
“…Literature also describes a high frequency of auditory and visual deficit among the elderly 11,12 , a fact that while not quantified in the present study, was observed, though not described. Reports of embarrassment at initiating and maintaining conversations and avoiding leaving home were constant, which can lead to social isolation, loss of occupational roles, mobility limitations, fragility and dependence.…”
Section: Discussioncontrasting
confidence: 46%
“…This loss of visual acuity can cause loss of balance, as the eyes are sensorial organs that provide most environmental information (9) . In addition, studies on the elderly identifi ed a high prevalence of visual defi cit (81.4%) and a high fall rate (54.2%) among those with this defi cit (15) . Patients with diminished muscle strength in their arms and legs showed an association with falls during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…According to Lee et al, decreased visual acuity is the second symptom of greater impact in the QOL, second only to breathing difficulties (4) . Consequent to cataract, there is a decrease of visual communication, thus increasing the risk for falls in this population (7,8) , because in parallel comes decreased stability, balance, perception of distance and depth, and adaptation to dark, which results in difficulties for the recognition of impending dangers (3,9,10) . Elderly in this condition, struggling to remain stable facing complex environments and tasks, have two times more chances to fall (9,11) .…”
mentioning
confidence: 99%